Parental preferences for vesicoureteral reflux treatment: Profile case best-worst scaling. Issue 1 (February 2021) - Dionise, Zachary R.; Gonzalez, Juan Marcos; Garcia-Roig, Michael L.; Kirsch, Andrew J.; Scales, Charles D.; Wiener, John S.; Purves, J. Todd; Routh, Jonathan C.
Summary: Introduction: Vesicoureteral reflux is a common pediatric urologic condition that often has several reasonable treatment options depending on condition severity. In order to choose the best treatment for their child, parents are expected to make judgements that weigh attributes such as treatment cost, effectiveness, and complication rate. Prior research has shown that factors such as treating hospital and surgeon also influence patient treatment choice. Objectives: This study evaluates parental preferences for reflux treatment using profile case best-worst scaling, an emerging technique in both urologic and health care preference estimation. The study also uses latent class analysis (LCA) to identify parental sub-classes with different preferences. Study design: Data were collected from a community sample of parents via a multimedia best-worst scaling survey instrument published to Amazon's Mechanical Turk online community. After extensive review of the literature, reflux attributes and attribute levels were selected to correspond with available treatments. The profile case best-worst scaling exercise elicited preferences for granular attributes of reflux treatments. Data were analyzed using multinomial logistic regression and class analysis to distinguish preference heterogeneity. Probability scaled values (PSVs) reflected the order of desirability of the attributes. Attribute preference importance was rescaled into dollar units for comparison as well. Results: We analyzed data for 248 respondents. The highest treatment effectiveness was more desirable than all other leveled treatment attributes (PSV 17.8, all p < 0.01) (Table). Low complication rate and doctor recommendation were amongst the other most desirable treatment attributes (PSV 11.3 and 9.0, respectively). Latent class analysis identified a class with more extreme preferences, for whom doctor recommendation and avoiding hospitalization were particularly desirable. Discussion: In this community-based sample, high treatment effectiveness and low complication rate were the most desirable treatment attributes to parents, though parents likely have heterogenous treatment preference structures. Shared parent-physician decision-making that incorporates parental preferences will likely allow more effective, targeted decision-making in the future. Summary Table 1 Profile Case Best Worst Scaling Table 1 Attribute Level Logit 95% CI∗∗ PSV∗∗∗ Effectiveness   53 percent −2.639 (-2.831, −2.447) 0.39   77 percent −0.178 (-0.372, 0.016) 3.76   88 percent 1.378 (1.190, 1.566) 10.52   97 percent 3.274 (3.053, 3.495) 17.76 Societal Cost   $1343 0.380 (0.181, 0.579) 5.77   $6365 −1.046 (-1.247, −0.846) 1.77   $7059 −1.265 (-1.464, −1.067) 1.45   $9556 −1.800 (-1.994, −1.605) 0.87 All complication rate   <1 percent 1.538 (1.346, 1.730) 11.32   4 percent 0.215 (0.015, 0.415) 5.12   10 percent −1.446 (-1.640, −1.252) 1.22   13 percent −1.720 (-1.914, 1.525) 0.94 Length of hospital stay   No visit to hospital 0.421 (0.218, 0.623) 5.94   Same day outpatient hospitalization 0.585 (0.386, 0.783) 6.65   1 day (overnight, home next day) −0.496 (-0.699, −0.293) 2.88   2 days −1.010 (-1.212, −0.807) 1.83 Doctor recommends   Yes 1.078 (0.909, 1.248) 9.00   No −1.856 (-2.027, −1.685) 0.83 Cosmetic appearance and Invasiveness   No scar and no invasive procedure N/A∗ N/A 4.34   No scar and endoscopic intervention with anesthesia −0.042 (-0.251, 0.167) 4.20   MIS with anesthesia and small scars −0.807 (-1.014, −0.600) 2.20   Open surgery with anesthesia and large scar −1.427 (-1.623, −1.227) 1.24 Profile case MNL model constructed using leveled attributes. ∗ Reference coefficient for MNL. ∗∗95% CI - 95% confidence interval. ∗∗∗PSV – probability scaled value.